Predator recognition learning in rainbow darters Etheostoma caeruleum: specific learning and neophobia. Issue 3 (20th June 2016) - Abudayah, W. H.; Mathis, A.
Abstract : This study investigated whether rainbow darters Etheostoma caeruleum can learn to recognize unfamiliar predators through the process of classical conditioning. Etheostoma caeruleum were conditioned by exposing them simultaneously to their chemical alarm cues (a known fright stimulus) and either chemical cues from larval ringed salamanders Ambystoma annulatum (unfamiliar predator) or to a blank water cue (control). Conditioning could result in either specific learning of the A. annulatum cue or increased wariness in response to any novel cue (neophobia). To distinguish between these possibilities, E. caeruleum in both groups were exposed to either A. annulatum cues alone or to chemical cues from western rat snakes Pantherophis obsoletus (novel cue) 2 days after conditioning. Treatment ( A. annulatum ‐conditioned) E. caeruleum, but not control E. caeruleum, showed a fright response when they were exposed to both the conditioned ( A. annulatum ) and novel ( P. obsoletus ) cues, indicating increased sensitivity to new stimuli. When E. caeruleum were retested after an additional 32 days, however, the fright response occurred only following exposure to the conditioned ( A. annulatum ) stimulus, indicating that specific learning of the A. annulatum cue had been retained whereas the neophobia to novel stimuli was temporary.